Science and mathematics instruction for emergent bilinguals through children’s literature - Alison Mcewin; Faye Bruun; David Daniel Jimenez; Carmen Tejeda-Delgado (Frontiers in Education)
Language acquisition, reading comprehension, and teacher PD will be presented in this article to discuss how the three components can be helpful in supporting emergent bilinguals (EBs). Using children’s literature in mathematics classes could improve the performance of (EB) students. The most current research suggests students who engage more with language through meaningful experiences like stories have greater retention for the material they are learning while they also see the English language in action. The more interaction and exposure to the language may increase EBs performance in the class subjects of English Language Arts and Reading. One of the best ways to engage emergent bilingual students with science and mathematics while supporting language acquisition is the use of children’s literature to teach science, technology, engineering, art, and math (STEAM) concepts. The elements of a story help students learn the structure of English usage in everyday speech while giving them solid STEAM concepts they can more easily understand through the story. This strategy also allows the teacher to scaffold for EB students using the story as a building block. By selecting and pairing effective EB strategies with children’s STEAM literature, there may be an increase in student performance overall.